THE USE OF CBCT-PAI INDEX IN THE ASSESSMENT OF CHRONIC PERIAPICAL LESIONS - Mihaela Sălceanu; Maria Vataman; Liana Aminov; Giuroiu Cristi; Topoliceanu Claudiu; Anca Melian (Romanian Society of Oral Rehabilitation, 2016)
The aim was to assess the CBCT-PAI index performance in the chronic periapical lesions diagnosis and evolution monitoring before and 3 months post-treatment. Material and methods. The study was performed on a group of 10 teeth diagnosed with chronic periapical lesions. CBCT were recorded before and after 3 months of endodontic treatment. Ez3D 2009 Plus software allowed the accurate measurement of bone lesions before and 3 months after treatment. The changes of CBCTPAI index after endodontic treatment were assessed by recording mean values, minimum and maximal values. Results. CBCT-PAI mean value lowest decrease was recorded for the coronal-apical slice (18.62%), while CBCT-PAI highest decrease was recorded for buccal-lingual slice (28.44%). Regarding maximum and minimal values, CBCT-PAI lowest decrease was recorded for the coronalapical slice (2.71%), while CBCT-PAI highest decrease was recorded for the buccal-lingual slice (39.70%). Conclusions. CBCT-PAI index can be used as a reliable and accurate tool in the diagnosis and the assessment of periapical lesions post-treatment evolution.